Evaluating the Construction and Limitations of Opportunism Principle in Indonesian Judiciary: Mengevaluasi Konstruksi dan Keterbatasan Asas Oportunisme dalam Peradilan di Indonesia - Ishwara, Ade Sathya Sanathana (Rechtsidee, 2023)
This research scrutinizes the construction, limitations, and parameters of the opportunism principle concerning public interest within the framework of progressive law in Indonesia, employing a normative legal research methodology. The study intricately analyzes legislative regulations through the lens of progressive law theory, incorporating primary legal materials such as the 1945 Constitution of the Republic of Indonesia, the Criminal Procedure Code, and the laws governing the Judiciary and the Prosecution Service. The preliminary findings indicate a nebulous state in the conceptual evolution of the opportunism principle in Indonesia, characterized by a lack of explicit standards and limitations in its implementation. Furthermore, the study identifies a pressing need for a more stringent selection mechanism and orientation towards the opportunism principle for prospective Attorney Generals to foster legal certainty and diminish community legal uncertainty. This study aims to contribute towards fostering a robust jurisprudential foundation, enhancing the role and moral authority of the Attorney General in the criminal justice system.Highlights: Conceptual Ambiguity: Current ambiguities in the opportunism principle necessitate clearer implementation standards in Indonesia. Legal Reforms: The study advocates for pivotal legal reforms to bolster the Attorney General's moral authority and role within the justice system. Implications on the Attorney General's Role: The research highlights the necessity for improved training and stricter selection procedures for prospective Attorney Generals. Keywords: Opportunism Principle, Progressive Law, Indonesian Judiciary, Legal Certainty, Attorney General